Faktor-Faktor Yang Mempengaruhi Keputusan Calon Pembeli Dalam Melakukan Pembelian Apartemen Mewah di Surabaya - Williams Dennis Masamitsu; Timoticin Kwanda; Jani Rahardjo (Dimensi Utama Teknik Sipil, 2019)
Williams Dennis Masamitsu: Postgraduate Thesis Factors That Influence Prospective Buyer's Decisions to Buy Luxury Apartment in Surabaya This research aims to find out factors that influence prospective buyer’s decision to buy luxury apartment in Surabaya. Data which were collected through online survey from 68 respondent from various city in Indonesia who have the desire to buy luxury apartments in Surabaya. Research gap in this study is that researchers add 2 new variables that have not been studied before. These variables are the another apartments costs and property management. This type of research is quantitative causal. This research used regression models to analyze the effect of price and scheme, another apartment costs, motivation, lifestyle, environment and relation, location, facility, building design and structure, property management, and promotion on prospective buyers to buying decision to luxury apartment in Surabaya. The result showed that simultaneously all the variable have positive and significant influence on consumer buying decision. Partially, the result showed that environment and relation, building design and structure, and property management has the most dominant effect on prospective buying